Kesenian Didong Sebagai Media Komunikasi Dan Pelestarian Pendidikan Karakter Masyarakat Gayo - Maulidha SA; Habiburridho (Jumper: Journal of Educational Multidisciplinary Research, 2024)
In general, many people interpret Didong art as a performing art that aims to entertain. However, basically Didong art can be interpreted as more than that, because in the poems of Didong art there are many things that can be communicated to society. This research aims to find out the role of Didong as a communication medium for the Gayo community, what things can be communicated through Didong art. The research method used is library research through the stages of preparing literature and recording the information needed in the research. The results of the literature review are that Didong art is viewed by the Gayo community not only as entertainment, but as a medium for communication, containing character education values including preserving customs and culture, moral values, Pancasila values, and as a means of conveying criticism, suggestions and input to the government.